OPTIMIZATION OF DRUG SUPPLY OFFICER HEMOGLOBIN LEVELS ON THE IMPROVEMENT OF PREGNANT WOMEN WITH ANDROID BASED ANEMIA - LISMAWATI; SEPTINORA, RICA TRI (International Journal of Current Pharmaceutical Research, 2020)
Objective: According to WHO, 40% of the maternal mortality rate in developing countries about the incidence of anemia in pregnancy. The incidence of anemia in pregnancy is caused by iron deficiency and acute hemorrhage. The frequency of pregnant women in Indonesia who are anemic are still very high at 63.5% compared to only 6% in the United States [1]. The aim of this research to determine differences in hemoglobin levels before and after supervised by officers to take medication to increase hemoglobin levels in pregnant women with anemia. Methods: The research was quasi-experiment using the control group conducted on July 11, s/d August 15th, 2019. The sample in this study was 30 respondents as the experimental group and 30 respondents as a control group, starting with the measurement of hemoglobin of respondents then monitoring the group given the intervention officer taking medication through an android-based application and subsequently re-measured hemoglobin level. Data were analyzed by univariate and bivariate through t-test with α = 0.05. Results: The result of the univariate analysis showed the average value of maternal age, parity and gestational age is homogeneous with p-value>0.05, which means there is no difference in the characteristics of groups of officers taking medication and without officers taking medication, and the bivariate analysis in getting p-value<0.001 so as to conclude that there are differences in hemoglobin level difference in the group taking medication and the clerk without officers taking medication. Conclusion: The conclusion of this research was hemoglobin levels increased in pregnant women with anemia after supervised by officers to take medication and increasing regularity in consuming Fe tablets in pregnant women.